Evolutionary Origin of the Carotenoid Cleavage Oxygenase Family in Plants and Expression of Pepper Genes in Response to Abiotic Stresses - Yao, Yixiu; Jia, Li; Cheng, Yuan; Ruan, Meiying; Ye, Qingjing; Wang, Rongqing; Yao, Zhuping; Zhou, Guozhi; Liu, Jia; Yu, Jiahong; Zhang, Peng; Yin, Yuhe; et al. (Frontiers in Plant Science, 2022)
Plant carotenoid cleavage oxygenase (CCO) is an enzyme that catalyzes the synthesis of carotenoids and participates in many important physiological functions. The plant CCOs exists in two forms, namely CCD (carotenoid cleavage dioxygenase) and NCED (nine-cis epoxide carotenoid dioxygenase). Although studies have shown that this gene family has been identified in many species, such as arabidopsis, grape, tomato, evolutionary origin of the CCO family and expression pattern of pepper genes in response to H2O2 and other abiotic stresses are still unclear. In this study, we used bioinformatics method to identify and analyze the members of CCO gene family from pepper and other 13 plants from lower to higher plant species based on the whole genome sequence. A total of 158 CCO genes were identified in different plant species and further divided into two groups (e.g. Group I and II). The former was subdivided into CCD7 and CCD8, and have independent evolutionary origins, respectively, while the latter was subdivided into CCD1, CCD4, CCD-like and NCED, which may have come from a common ancestor. In addition, the results of RNA-seq showed that the expression patterns of pepper CaCCO genes were different in the tissues tested and only several genes were expressed at high levels such as CaCCD1a, CaCCD4a, CaNCED3, and CaCCD1b. For H2O2 and other abiotic stresses, such as plant hormones, heat, cold, drought, and Nacl treatments, induction of about half of the CaCCO genes were observed. Moreover, the expression patterns of CaCCOs were further investigated under heat, cold, drought and Nacl treatments by qRT-PCR, and most members were responsive to these stresses, especially some CaCCOs with significant expression changes were identified, such as CaCCD4c, CaCCD-like1, CaCCD8 and CaCCD1b, suggesting the important roles of CaCCOs in abiotic stress responses. All these results will provide a valuable analytical basis for understanding the evolution and functions of CCO family in plants.